“Die Internationale”: from Protest Song to Official Anthem and Back : Aspects of the German Reception of “L’Internationale” in the Early 1900s and After 1945 - Ceuppens, Jan (chronotopos – A Journal of Translation History, 2025)
The fate of the German translations of “L’Internationale” reflects some of the fates of the German left. Several translations were produced around 1900, before the Emil Luckhardt version would become canonized shortly after the First World War. When compared to a more scholarly translation–of which the very first one, by Sigmar Mehring, is a good example–, Luckhardt’s is much less faithful to the Pottier original, but still quite effective. It is also less ideologically radical, so that it was acceptable within many strands of the German left. After the establishment of two German states following the Second World War, and even after the German unification in 1990, the song became a point of dispute for the left, even if at the same it also lost much of its original message in popular culture. This article examines the possible reasons for the lasting success of Luckhardt’s translation, its shifts in relation to the source text and some of the contexts in which it has been used.